2014
DOI: 10.1002/lsm.22258
|View full text |Cite
|
Sign up to set email alerts
|

Optical clearing agent perfusion enhancement via combination of microneedle poration, heating and pneumatic pressure

Abstract: Background and Objective: Optical clearing agents (OCAs) have shown promise for increasing the penetration depth of biomedical lasers by temporarily decreasing optical scattering within the skin. However, their translation to the clinic has been constrained by lack of practical means for effectively perfusing OCA within target tissues in vivo. The objective of this study was to address this limitation through combination of a variety of techniques to enhance OCA perfusion, including heating of OCA, microneedli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…These agents are commonly known as SOCAs (skin optical clearing agents) and generally adjust skin refractive indexes and induce packaging of scatterers such as collagen fibers ( Tuchina et al., 2019 ) by dehydration-driven reduction of skin thickness ( Wen et al., 2010 ). Several penetration enhancers are widely used to facilitate their diffusion and improve their clearing power; they can be classified into chemical penetration enhancers such as propylene glycol, DMSO ( Zaytsev et al., 2020 ), ethanol ( Zaytsev et al., 2020 ), azone ( Zhao et al., 2016 ), dimethyl sulfoxide ( Genina et al, 2020 ), oleic acid ( Zaytsev et al., 2020 ), and thiazone ( Zaytsev et al., 2020 ) (the last four ones achieve penetration enhancement by dissolving Stratum Corneum lipids) ( Zaytsev et al., 2020 ), and physical penetration enhancers, such as ultrasounds (sonophoresis) ( Genina et al, 2020 ), microneedles ( Yoon et al., 2010 ), lasers (FLMA, fractional laser microablation) ( Genina et al., 2020a ), pneumatic pressure ( Damestani et al., 2014 ), heat ( Damestani et al., 2014 ), or abrasive instruments (microdermabrasion) ( Genina et al, 2020 ). Different combinations of penetration enhancers have been applied to improve the efficacy of several clearing agents.…”
Section: Translational Applications Of Tissue Clearing and 3d Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…These agents are commonly known as SOCAs (skin optical clearing agents) and generally adjust skin refractive indexes and induce packaging of scatterers such as collagen fibers ( Tuchina et al., 2019 ) by dehydration-driven reduction of skin thickness ( Wen et al., 2010 ). Several penetration enhancers are widely used to facilitate their diffusion and improve their clearing power; they can be classified into chemical penetration enhancers such as propylene glycol, DMSO ( Zaytsev et al., 2020 ), ethanol ( Zaytsev et al., 2020 ), azone ( Zhao et al., 2016 ), dimethyl sulfoxide ( Genina et al, 2020 ), oleic acid ( Zaytsev et al., 2020 ), and thiazone ( Zaytsev et al., 2020 ) (the last four ones achieve penetration enhancement by dissolving Stratum Corneum lipids) ( Zaytsev et al., 2020 ), and physical penetration enhancers, such as ultrasounds (sonophoresis) ( Genina et al, 2020 ), microneedles ( Yoon et al., 2010 ), lasers (FLMA, fractional laser microablation) ( Genina et al., 2020a ), pneumatic pressure ( Damestani et al., 2014 ), heat ( Damestani et al., 2014 ), or abrasive instruments (microdermabrasion) ( Genina et al, 2020 ). Different combinations of penetration enhancers have been applied to improve the efficacy of several clearing agents.…”
Section: Translational Applications Of Tissue Clearing and 3d Imagingmentioning
confidence: 99%
“…Besides, it has been shown that combined application of microneedles and sonophoresis can enhance diffusion rate of 70% glycerol up to 2.3-fold compared with microneedling alone ( Yoon et al., 2010 ) and that FLMA in combination with sonophoresis highly increases clearing speed of PEG-300 ( Genina et al., 2020a ). Additionally, combination of skin cleaning, microdermabrasion, sonophoresis, and glycerol application allowed improved signal detection in photoacoustic flow cytometry ( Menyaev et al., 2013 ), and merging of propylene glycol, heated to 45°C, microneedling, vacuum pre-treatment, and application of positive pressure increased porcine skin transparency up to 25% ( Damestani et al., 2014 ).…”
Section: Translational Applications Of Tissue Clearing and 3d Imagingmentioning
confidence: 99%
“…However, in realistic in vivo applications, the optical clearing effect of agents is sometimes unsatisfactory due to the dense stratum corneum seriously hindering agent penetration into the skin. To overcome this barrier, researchers have proposed various physical methods to promote the penetration of OCAs, including laser irradiation, 13 fractional laser microablation, 34 adhesive tape stripping, 35 sandpaper rubbing, 36 sonophoresis, 37 microneedle, 38 flashlight irradiation, 39 and more. These methods enhance the OCA penetration by directly removing the stratum corneum and part of the living epidermis, creating microchannels in the skin or generating heat effects to locally disrupt the stratum corneum.…”
Section: In Vivo Skin Optical Clearing Methodsmentioning
confidence: 99%
“…Using optical coherence tomography (OCT), we demonstrated the initial feasibility of nc‐YSZ cranial implants within the context of cortical imaging of an acute murine model . For optical clearing of the scalp temporarily, our study on delivery techniques of optical clearing agents (OCA) such as propylene glycol (PG) showed that the combination of heated PG, microneedling and vacuum pretreatments, and positive pressure post‐treatment significantly enhanced the perfusion of this topically applied OCA .…”
Section: Introductionmentioning
confidence: 99%